Phase change energy storage-heat conduction synergistic aluminum-based composite material and preparation method thereof
By introducing multi-scale thermal conductivity networks and interface coupling agents into phase change materials and adopting innovative preparation processes, the problems of poor interface compatibility, discontinuity of thermal conductivity and insufficient thermal cycle stability of existing materials are solved, and the coordinated enhancement of energy storage, thermal conductivity and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411801229.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
The existing phase change materials and thermal filler composite materials have problems such as poor interface compatibility, discontinuity of thermal network, insufficient thermal cycle stability and insufficient mechanical properties.
By combining phase change energy storage materials, multi-scale thermal conductivity fillers, interface coupling agents and aluminum matrix, and using the preparation process of mechanical alloying and discharge plasma sintering, a multi-scale thermal conductivity network is constructed and the interface structure is optimized.
The coordinated enhancement of energy storage, thermal conductivity and mechanical properties is achieved, which significantly improves the thermal conductivity, thermal cycle stability and mechanical properties of the material, and extends the service life of the material.
Smart Images

Figure BDA0005178097520000141 
Figure BDA0005178097520000142 
Figure BDA0005178097520000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum-based composite materials, and in particular to a phase-change energy storage-heat conduction synergistic aluminum-based composite material and a preparation method thereof. Background Art
[0002] With the rapid development of modern science and technology, thermal management has become a key bottleneck restricting the progress of many high-tech fields. Especially in the fields of aerospace, electronic cooling and new energy vehicles, higher and higher requirements are placed on the thermal conductivity and thermal stability of materials. Traditional single-function materials can no longer meet the needs of these complex application scenarios. Therefore, the development of new composite materials with multifunctional synergistic effects has become a research hotspot in the current field of materials science.
[0003] In the prior art, researchers have tried to compound phase change materials with thermal conductive fillers to achieve the dual functions of energy storage and heat conduction. However, this type of composite material still faces many challenges. First, the interface compatibility between phase change materials and thermal conductive fillers is poor, resulting in low heat transfer efficiency. Secondly, the dispersion of thermal conductive fillers in the matrix is poor, making it difficult to form a continuous heat conduction network. Furthermore, during the thermal cycle process, the performance stability of the material is insufficient, and performance degradation is prone to occur after long-term use. In addition, while existing composite materials improve thermal conductivity, they often sacrifice the mechanical strength of the material, limiting its application in high-stress environments. Summary of the invention
[0004] Based on the above problems, the present invention proposes a phase-change energy storage-thermal conductivity synergistic aluminum-based composite material and its preparation method. The material successfully achieves synergistic enhancement of energy storage, thermal conductivity and mechanical properties by ingeniously compounding phase-change energy storage materials, multi-scale thermal conductive fillers, interface coupling agents and aluminum matrix, and adopts an innovative preparation process.
[0005] The object of the present invention is to provide a thermal self-repairing antibacterial aerospace capsule composite material, which comprises the following components in parts by weight:
[0006] Aluminum matrix 75-90 parts;
[0007] 8-20 parts of phase change energy storage material;
[0008] 2-5 parts of thermal conductivity enhancer;
[0009] 0.5-2 parts of carbon nanotubes;
[0010] Interface coupling agent 0.2-1 part;
[0011] Dispersant 0.1-0.5 parts.
[0012] Preferably, the aluminum matrix is Al-Si-Mg aluminum alloy powder with a particle size range of 20-80 μm.
[0013] Preferably, the phase change energy storage material is paraffin with a melting point of 52-54°C.
[0014] Preferably, the thermal conductivity enhancer is aluminum nitride powder with a particle size of 1-5 μm.
[0015] Preferably, the carbon nanotubes are multi-walled carbon nanotubes with an outer diameter of 20-40 nm and a length of 10-30 μm.
[0016] Preferably, the interface coupling agent is 3-aminopropyltriethoxysilane.
[0017] Preferably, the dispersant is polyvinyl pyrrolidone with a molecular weight of 40,000-360,000.
[0018] The method for preparing the phase-change energy storage-thermal conduction synergistic aluminum-based composite material comprises the following steps:
[0019] (1) Composite powder preparation:
[0020] First, the carbon nanotubes and thermal conductivity enhancer are dispersed in anhydrous ethanol and ultrasonically dispersed for 45-60 minutes;
[0021] Secondly, add the interfacial coupling agent and stir the reaction at 65-75°C for 3-5 hours;
[0022] Then, filter, wash and dry;
[0023] Again, the dried powder is mixed with a dispersant and dry-milled in a planetary ball mill at 250-300 rpm for 2-4 hours;
[0024] (2) Phase change material composite:
[0025] First, the phase change energy storage material is heated to 60-70°C to completely melt it;
[0026] Secondly, slowly adding the composite powder prepared in step (1) into the molten phase change energy storage material while stirring;
[0027] Then, high-speed shear mixing was performed at 65-75°C for 40-60 minutes;
[0028] Finally, the mixture was cooled to room temperature and ground into a fine powder;
[0029] (3) Preparation of aluminum-based composite materials:
[0030] First, the aluminum matrix is mixed with the phase change material composite powder prepared in step (2);
[0031] Secondly, mechanical alloying was performed at a speed of 250-300 rpm for 8-12 hours under argon protection;
[0032] Then, the mixed powder is loaded into a graphite mold and densified by spark plasma sintering process under inert gas protection;
[0033] (4) Post-processing:
[0034] First, the sintered samples were surface machined;
[0035] Secondly, solution treatment at 380-420°C for 1-2 hours under nitrogen atmosphere, followed by water quenching;
[0036] Finally, aging treatment is performed at 160-180°C for 4-6 hours.
[0037] Preferably, the parameters of the spark plasma sintering process are:
[0038] Heating rate 50-100℃ / min;
[0039] Maximum temperature 500-530℃;
[0040] Keep warm for 5-10 minutes;
[0041] Pressure 40-50MPa;
[0042] The cooling rate was natural cooling to room temperature.
[0043] Preferably, the method further comprises the following steps:
[0044] In step (2), the phase change material composite is ground to a particle size less than 100 μm.
[0045] The core innovation of the present invention is:
[0046] 1. Multi-scale thermal conductive network design: By introducing carbon nanotubes and aluminum nitride powder as thermal conductive fillers, a multi-level thermal conductive network from nanometer to micrometer scale is constructed. Carbon nanotubes form nanoscale heat conduction channels with their high aspect ratio and excellent axial thermal conductivity. Micrometer-scale aluminum nitride powder fills the gaps between carbon nanotubes, further improving the continuity and effectiveness of the thermal conductive network. This multi-scale structural design significantly improves the overall thermal conductivity of the composite material, while also unexpectedly enhancing the mechanical properties of the material.
[0047] 2. Interface control technology: The present invention uses 3-aminopropyltriethoxysilane as an interface coupling agent to achieve interface optimization between organic phase change materials, inorganic thermal conductive fillers and aluminum substrates. The alkyl chain of the silane coupling agent forms a physical entanglement with the phase change material, while its siloxy group forms a chemical bond with aluminum nitride and the aluminum substrate. This unique interface structure not only reduces the interface thermal resistance and improves the heat transfer efficiency, but also significantly enhances the interface bonding strength of the material, thereby improving the mechanical properties and long-term stability of the composite material.
[0048] 3. Innovative preparation process: The present invention adopts a preparation method combining mechanical alloying with spark plasma sintering, which overcomes the problems of uneven filler dispersion and poor interface bonding in traditional processes. During the mechanical alloying process, high-energy ball milling not only achieves uniform mixing of the components, but also may cause mechanical alloying of the material at the nanoscale, forming a more stable composite structure. The spark plasma sintering technology achieves rapid densification of the material at a lower temperature through rapid heating and pressure application, effectively inhibits grain growth, and maintains the characteristics of the nanostructure.
[0049] 4. Multiple functions of phase change materials: The phase change materials in the present invention not only play the role of energy storage, but also inadvertently play the role of stress buffering and self-repairing. During the thermal cycle, the melting-solidification process of the phase change material can relieve thermal stress and reduce the formation of microcracks in the material. At the same time, the molten phase change material can also fill tiny cracks and solidify again during the cooling process, achieving a certain degree of self-repairing function.
[0050] Through the above innovative design, the present invention successfully solves the problems existing in the prior art, such as large interface thermal resistance, discontinuous thermal network, poor thermal cycle stability, and insufficient mechanical properties. More importantly, the present invention achieves synergistic enhancement of energy storage, thermal conductivity, and mechanical properties, breaking through the limitation of traditional composite materials where performance increases and decreases at the same time.
[0051] The beneficial effects of the present invention are mainly reflected in the following aspects:
[0052] 1. Excellent thermal conductivity: Through the multi-scale thermal network design, the thermal conductivity of the composite material of the present invention can reach up to 195.6W / m·K, which is 30-50% higher than the existing technology. This performance improvement provides a new possibility for solving the heat dissipation problem of high heat flux density equipment.
[0053] 2. Excellent phase change energy storage properties: While ensuring high thermal conductivity, the material of the present invention still maintains considerable phase change latent heat (up to 41.5 J / g). This synergistic effect of energy storage and thermal conductivity enables the material to perform well in environments with large temperature fluctuations and can effectively alleviate thermal shock.
[0054] 3. Excellent thermal cycle stability: After 2000 thermal cycles, the material of the present invention still maintains more than 96% of its performance, far exceeding the existing technology. This excellent long-term stability greatly extends the service life of the material and reduces maintenance costs.
[0055] 4. Significantly improved mechanical properties: The material of the present invention not only has excellent thermal properties, but also has significantly improved mechanical properties. The tensile strength of the optimal formula reaches 325MPa, which is 30% higher than that of the traditional method. This "thermal-mechanical" synergistic enhancement effect greatly expands the application range of the material.
[0056] 5. Unexpected self-healing ability: During the research process, we unexpectedly discovered that the material has a certain self-healing ability. This property stems from the unique role of phase change materials in the thermal cycle process, which further enhances the reliability and service life of the material.
[0057] In general, the phase-change energy storage-thermal conductivity synergistic aluminum-based composite material developed by the present invention has successfully achieved synergistic enhancement of energy storage, thermal conductivity and mechanical properties through multi-scale structural design, interface control technology and innovative preparation process. This multifunctional integrated design concept not only solves many problems existing in the prior art, but also provides new ideas and methods for the development of a new generation of thermal management materials. In view of its excellent comprehensive performance, the material of the present invention is expected to find wide application in high-end fields such as aerospace, electronic cooling, and new energy vehicles, making important contributions to the technological upgrading and sustainable development of related industries. DETAILED DESCRIPTION
[0058] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0059] Example 1: Phase change energy storage-thermal conduction synergistic aluminum-based composite material and preparation method thereof
[0060] The phase change energy storage-thermal conductivity synergistic aluminum-based composite material of this embodiment includes the following components by weight: 75 parts of aluminum matrix, 20 parts of phase change energy storage material, 5 parts of thermal conductivity enhancer, 0.5 parts of carbon nanotubes, 1 part of interface coupling agent, and 0.5 parts of dispersant.
[0061] The preparation method of the material comprises the following steps:
[0062] (1) Preparation of composite powder: First, 0.5 parts of multi-walled carbon nanotubes (outer diameter 20nm, length 10μm) and 5 parts of aluminum nitride powder (particle size 1μm) were dispersed in 200mL of anhydrous ethanol and ultrasonically dispersed for 60 minutes. Secondly, 1 part of 3-aminopropyltriethoxysilane was added and stirred at 65°C for 5 hours. Then, it was filtered, washed with ethanol 5 times, and vacuum dried at 70°C for 15 hours. Again, the dried powder was mixed with 0.5 parts of polyvinyl pyrrolidone (molecular weight 40,000) and dry-milled in a planetary ball mill at 250rpm for 4 hours.
[0063] (2) Phase change material compounding: First, heat 20 parts of paraffin wax (melting point 52°C) to 60°C to completely melt it. Secondly, slowly add the composite powder prepared in step (1) to the molten paraffin wax while stirring. Then, high-speed shear mixing is performed at 65°C for 60 minutes to ensure that the powder is evenly dispersed in the phase change material. Finally, the mixture is cooled to room temperature and ground into a fine powder (particle size <100μm).
[0064] (3) Preparation of aluminum-based composite materials: First, 75 parts of A356 aluminum alloy powder (particle size 20 μm) were mixed with the phase change material composite powder prepared in step (2). Secondly, mechanical alloying was performed at a speed of 250 rpm for 12 hours under argon protection. Then, the mixed powder was loaded into a graphite mold and densified by spark plasma sintering under inert gas protection. The parameters of the spark plasma sintering process were: heating rate 50°C / min, maximum temperature 500°C, holding time 10 minutes, pressure 40 MPa, and natural cooling to room temperature.
[0065] (4) Post-treatment: First, the sintered samples were surface machined to remove the surface oxide layer. Then, they were solution treated at 380°C for 2 hours in a nitrogen atmosphere, and then water quenched. Finally, they were aged at 160°C for 6 hours.
[0066] Preferably, in the embodiment of the present invention, aluminum nitride powder is introduced as a thermal conductivity enhancer to form a multi-scale thermal conductive network with carbon nanotubes, thereby significantly improving the overall thermal conductivity of the composite material. At the same time, 3-aminopropyltriethoxysilane is used as an interface coupling agent, which not only improves the interface bonding between the inorganic filler and the organic phase change material, but also forms a chemical bond with the aluminum matrix through the amino group, further enhancing the overall performance of the material.
[0067] Example 2: Phase change energy storage-thermal conduction synergistic aluminum-based composite material and preparation method thereof
[0068] The phase change energy storage-thermal conductivity synergistic aluminum-based composite material of this embodiment includes the following components by weight: 90 parts of aluminum matrix, 8 parts of phase change energy storage material, 2 parts of thermal conductivity enhancer, 2 parts of carbon nanotubes, 0.2 parts of interface coupling agent, and 0.1 parts of dispersant.
[0069] The preparation method of the material comprises the following steps:
[0070] (1) Preparation of composite powder: First, 2 parts of multi-walled carbon nanotubes (outer diameter 40nm, length 30μm) and 2 parts of aluminum nitride powder (particle size 5μm) were dispersed in 300mL of anhydrous ethanol and ultrasonically dispersed for 45 minutes. Secondly, 0.2 parts of 3-aminopropyltriethoxysilane were added and stirred at 75°C for 3 hours. Then, the mixture was filtered, washed with ethanol 3 times, and vacuum dried at 80°C for 10 hours. Again, the dried powder was mixed with 0.1 parts of polyvinyl pyrrolidone (molecular weight 360,000) and dry-milled at 300rpm in a planetary ball mill for 2 hours.
[0071] (2) Phase change material compounding: First, heat 8 parts of paraffin wax (melting point 54°C) to 70°C to completely melt it. Secondly, slowly add the composite powder prepared in step (1) to the molten paraffin wax while stirring. Then, high-speed shear mixing is performed at 75°C for 40 minutes to ensure that the powder is evenly dispersed in the phase change material. Finally, the mixture is cooled to room temperature and ground into a fine powder (particle size <100μm).
[0072] (3) Preparation of aluminum-based composite materials: First, 90 parts of A356 aluminum alloy powder (particle size 80 μm) were mixed with the phase change material composite powder prepared in step (2). Secondly, mechanical alloying was performed at a speed of 300 rpm for 8 hours under argon protection. Then, the mixed powder was loaded into a graphite mold and densified by spark plasma sintering under inert gas protection. The parameters of the spark plasma sintering process were: heating rate 100°C / min, maximum temperature 530°C, holding time 5 minutes, pressure 50 MPa, and natural cooling to room temperature.
[0073] (4) Post-treatment: First, the sintered samples were surface machined to remove the surface oxide layer. Then, they were solution treated at 420°C for 1 hour in a nitrogen atmosphere, and then water quenched. Finally, they were aged at 180°C for 4 hours.
[0074] Furthermore, in this embodiment, the thermal conductivity of the composite material is improved by increasing the content and size of carbon nanotubes and reducing the proportion of phase change materials. This adjustment of the composition ratio is conducive to forming a more continuous and efficient heat conduction network, thereby optimizing the thermal management capability of the material.
[0075] Example 3: Phase change energy storage-thermal conduction synergistic aluminum-based composite material and preparation method thereof
[0076] The phase change energy storage-thermal conductivity synergistic aluminum-based composite material of this embodiment includes the following components by weight: 82.5 parts of aluminum matrix, 14 parts of phase change energy storage material, 3.5 parts of thermal conductivity enhancer, 1.25 parts of carbon nanotubes, 0.6 parts of interface coupling agent, and 0.3 parts of dispersant.
[0077] The preparation method of the material comprises the following steps:
[0078] (1) Preparation of composite powder: First, 1.25 parts of multi-walled carbon nanotubes (outer diameter 30nm, length 20μm) and 3.5 parts of aluminum nitride powder (particle size 3μm) were dispersed in 250mL of anhydrous ethanol and ultrasonically dispersed for 52 minutes. Secondly, 0.6 parts of 3-aminopropyltriethoxysilane were added and stirred at 70°C for 4 hours. Then, the mixture was filtered, washed with ethanol 4 times, and vacuum dried at 75°C for 12 hours. Again, the dried powder was mixed with 0.3 parts of polyvinyl pyrrolidone (molecular weight 200,000) and dry-milled at 275rpm in a planetary ball mill for 3 hours.
[0079] (2) Phase change material compounding: First, heat 14 parts of paraffin wax (melting point 53°C) to 65°C to completely melt it. Secondly, slowly add the composite powder prepared in step (1) to the molten paraffin wax while stirring. Then, high-speed shear mixing is performed at 70°C for 50 minutes to ensure that the powder is evenly dispersed in the phase change material. Finally, the mixture is cooled to room temperature and ground into a fine powder (particle size <100μm).
[0080] (3) Preparation of aluminum-based composite materials: First, 82.5 parts of A356 aluminum alloy powder (particle size 50 μm) were mixed with the phase change material composite powder prepared in step (2). Secondly, mechanical alloying was performed at a speed of 275 rpm for 10 hours under argon protection. Then, the mixed powder was loaded into a graphite mold and densified by spark plasma sintering under inert gas protection. The parameters of the spark plasma sintering process were: heating rate 75°C / min, maximum temperature 515°C, holding time 7.5 minutes, pressure 45 MPa, and natural cooling to room temperature.
[0081] (4) Post-treatment: First, the sintered samples were surface machined to remove the surface oxide layer. Then, they were solution treated at 400°C for 1.5 hours in a nitrogen atmosphere, and then water quenched. Finally, they were aged at 170°C for 5 hours.
[0082] Preferably, in the embodiment of the present invention, by adjusting the ratio of the phase change material and the thermal conductivity enhancer, a balance between energy storage performance and thermal conductivity is achieved. This ratio design helps to maintain a high thermal conductivity while ensuring sufficient phase change latent heat, thereby meeting the needs of different application scenarios.
[0083] Example 4: Phase change energy storage-thermal conduction synergistic aluminum-based composite material and preparation method thereof
[0084] The phase change energy storage-thermal conductivity synergistic aluminum-based composite material of this embodiment includes the following components by weight: 87 parts of aluminum matrix, 10 parts of phase change energy storage material, 3 parts of thermal conductivity enhancer, 1 part of carbon nanotubes, 0.4 parts of interface coupling agent, and 0.2 parts of dispersant.
[0085] The preparation method of the material comprises the following steps:
[0086] (1) Preparation of composite powder: First, 1 part of multi-walled carbon nanotubes (outer diameter 35nm, length 25μm) and 3 parts of aluminum nitride powder (particle size 4μm) were dispersed in 275mL of anhydrous ethanol and ultrasonically dispersed for 55 minutes. Secondly, 0.4 parts of 3-aminopropyltriethoxysilane were added and stirred at 72°C for 3.5 hours. Then, the mixture was filtered, washed with ethanol 4 times, and vacuum dried at 77°C for 13 hours. Again, the dried powder was mixed with 0.2 parts of polyvinyl pyrrolidone (molecular weight 150,000) and dry-milled in a planetary ball mill at 280rpm for 3.5 hours.
[0087] (2) Phase change material compounding: First, heat 10 parts of paraffin wax (melting point 53.5°C) to 67°C to completely melt it. Secondly, slowly add the composite powder prepared in step (1) to the molten paraffin wax while stirring. Then, high-speed shear mixing is performed at 72°C for 55 minutes to ensure that the powder is evenly dispersed in the phase change material. Finally, the mixture is cooled to room temperature and ground into a fine powder (particle size <100μm).
[0088] (3) Preparation of aluminum-based composite materials: First, 87 parts of A356 aluminum alloy powder (particle size 65 μm) were mixed with the phase change material composite powder prepared in step (2). Secondly, mechanical alloying was performed at a speed of 285 rpm for 9 hours under argon protection. Then, the mixed powder was loaded into a graphite mold and densified by spark plasma sintering under inert gas protection. The parameters of the spark plasma sintering process were: heating rate 85°C / min, maximum temperature 520°C, holding time 8 minutes, pressure 47 MPa, and natural cooling to room temperature.
[0089] (4) Post-treatment: First, the sintered samples were surface machined to remove the surface oxide layer. Then, they were solution treated at 410°C for 1.7 hours in a nitrogen atmosphere, and then water quenched. Finally, they were aged at 175°C for 5.5 hours.
[0090] Furthermore, in this embodiment, the mechanical properties of the composite material are improved by optimizing the content of the aluminum matrix and the spark plasma sintering process parameters. This process adjustment helps to enhance the strength and toughness of the material while ensuring the thermal conductivity and energy storage performance, making it more suitable for use in high stress environments.
[0091] Comparative Example 1: Phase change energy storage-thermal conductive aluminum matrix composite material without carbon nanotubes
[0092] The composite material composition of this comparative example is the same as that of Example 1, but does not contain carbon nanotubes. The specific components (by weight) are: 75 parts of aluminum matrix, 20 parts of phase change energy storage material, 5 parts of thermal conductivity enhancer, 1 part of interface coupling agent, and 0.5 parts of dispersant.
[0093] The preparation method is basically the same as that in Example 1, but the steps related to carbon nanotubes are omitted. In the composite powder preparation stage, only aluminum nitride powder is used for processing. Other steps and parameters remain unchanged.
[0094] By comparing the thermal conductivity of Example 1 and this comparative example, it can be clearly observed that carbon nanotubes play a key role in forming a multi-scale thermal conductive network. The experimental results show that the thermal conductivity of the composite material lacking carbon nanotubes is reduced by about 30%, which fully proves the importance of the synergistic effect of carbon nanotubes and aluminum nitride powder in improving the thermal conductivity of the material.
[0095] Comparative Example 2: Phase change energy storage-thermal conductivity synergistic aluminum-based composite material without interfacial coupling agent
[0096] The composite material composition of this comparative example is the same as that of Example 2, but does not contain an interface coupling agent. The specific components (by weight) are: 90 parts of aluminum matrix, 8 parts of phase change energy storage material, 2 parts of thermal conductivity enhancer, 2 parts of carbon nanotubes, and 0.1 parts of dispersant.
[0097] The preparation method is basically the same as that of Example 2, but the step of adding 3-aminopropyltriethoxysilane is omitted in the composite powder preparation stage. Other steps and parameters remain unchanged.
[0098] By comparing the interface bonding strength and thermal cycle stability of Example 2 and this comparative example, the important role of the interface coupling agent can be clearly seen. The experimental results show that the thermal conductivity of the composite material without the interface coupling agent decreased by about 15% after 1000 thermal cycles, while the material of Example 2 only decreased by about 5%. This proves the key role of the interface coupling agent in improving the interface bonding between the inorganic filler and the organic phase change material and forming a chemical bond with the aluminum matrix, thereby improving the long-term stability of the material.
[0099] Comparative Example 3: Phase change energy storage and thermal conductivity synergistic aluminum-based composite material with high content of phase change material
[0100] The composition of the composite material of this comparative example is based on Example 3, but the content of the phase change energy storage material is significantly increased. The specific components (by weight) are: 67.5 parts of aluminum matrix, 29 parts of phase change energy storage material, 3.5 parts of thermal conductivity enhancer, 1.25 parts of carbon nanotubes, 0.6 parts of interface coupling agent, and 0.3 parts of dispersant.
[0101] The preparation method is basically the same as that of Example 3, except that the amount of paraffin wax is adjusted in the phase change material compounding stage. Other steps and parameters remain unchanged.
[0102] By comparing the energy storage capacity and thermal conductivity of Example 3 and this comparative example, the effect of the phase change material content on the material properties can be observed. The experimental results show that although the energy storage capacity of this comparative example is increased by about 40%, its thermal conductivity is reduced by about 25%. This result verifies the excellent balance achieved by the present invention between phase change energy storage and thermal conductivity, and proves the importance of a moderate phase change material content for maintaining a high thermal conductivity efficiency.
[0103] Comparative Example 4: Phase change energy storage-thermal conductivity synergistic aluminum-based composite material without thermal conductivity enhancer
[0104] The composite material composition of this comparative example is the same as that of Example 4, but does not contain a thermal conductivity enhancer (aluminum nitride powder). The specific components (by weight) are: 90 parts of aluminum matrix, 10 parts of phase change energy storage material, 1 part of carbon nanotubes, 0.4 parts of interface coupling agent, and 0.2 parts of dispersant.
[0105] The preparation method is basically the same as that of Example 4, but the step of adding aluminum nitride powder is omitted in the composite powder preparation stage. Other steps and parameters remain unchanged.
[0106] By comparing the thermal conductivity and thermal diffusivity of Example 4 and this comparative example, it can be clearly observed that the role of the thermal conductivity enhancer in improving the overall thermal conductivity of the material. The experimental results show that the thermal conductivity of the composite material without the thermal conductivity enhancer is reduced by about 20%, and the thermal diffusivity is reduced by about 15%. This fully demonstrates the synergistic effect of aluminum nitride powder and carbon nanotubes in forming an efficient thermal conductive network, and verifies the superiority of the multi-scale thermal conductive network design of the present invention.
[0107] Comparative Example 5: Phase change energy storage-thermal conductivity synergistic aluminum-based composite material prepared by traditional mechanical mixing method
[0108] The composite material composition of this comparative example is the same as that of Example 1, but is prepared by a traditional mechanical mixing method. The specific components (by weight) are: 75 parts of aluminum matrix, 20 parts of phase change energy storage material, 5 parts of thermal conductivity enhancer, 0.5 parts of carbon nanotubes, 1 part of interface coupling agent, and 0.5 parts of dispersant.
[0109] The preparation method is as follows:
[0110] (1) All components were mixed directly in a high-speed mixer at 300 rpm for 2 hours.
[0111] (2) The mixture was pressed into a mold by hot pressing at 400°C for 4 hours and a pressure of 200 MPa.
[0112] (3) After cooling to room temperature, perform surface treatment.
[0113] By comparing the microstructure and performance of Example 1 and this comparative example, the advantages of the preparation method of the present invention can be clearly seen. The experimental results show that in the composite material prepared by the traditional method, the carbon nanotubes and the thermal conductivity enhancer are unevenly distributed, resulting in a discontinuous thermal network. Its thermal conductivity is about 35% lower than that of Example 1, and its thermal cycle stability is poor. This verifies the importance of the mechanical alloying combined with the spark plasma sintering process in the present invention in achieving uniform dispersion and high density.
[0114] Comparative Example 6: Phase change energy storage-thermal conductivity synergistic aluminum-based composite material without dispersant
[0115] The composite material composition of this comparative example is the same as that of Example 3, but does not contain a dispersant. The specific components (by weight) are: 82.8 parts of aluminum matrix, 14 parts of phase change energy storage material, 3.5 parts of thermal conductivity enhancer, 1.25 parts of carbon nanotubes, and 0.6 parts of interface coupling agent.
[0116] The preparation method is basically the same as that of Example 3, but the step of adding polyvinyl pyrrolidone is omitted in the composite powder preparation stage. Other steps and parameters remain unchanged.
[0117] By comparing the filler dispersibility and thermal conductivity of Example 3 and this comparative example, the role of the dispersant can be observed. The experimental results show that the carbon nanotubes and aluminum nitride powders in the composite material without a dispersant are obviously agglomerated, resulting in a discontinuous thermal network. Its thermal conductivity is about 18% lower than that of Example 3, and the performance uniformity is poor. This proves the key role of the dispersant in improving the filler dispersibility and forming a continuous and efficient thermal conductive network, and verifies the innovation of the present invention in material design and preparation process.
[0118] Through the above six comparative examples, we have fully verified the importance of each key component and preparation process parameters of the present invention. These comparative experiments clearly demonstrate the synergistic effect of carbon nanotubes, thermal conductivity enhancers, interface coupling agents, dispersants and innovative preparation processes in achieving high-performance phase change energy storage-thermal conductivity synergistic aluminum-based composite materials. The experimental results fully demonstrate the innovation and superiority of the present invention in terms of multifunctional integration, interface regulation, multi-scale thermal conductive network construction and performance balance, and provide important scientific basis and technical support for the development of a new generation of thermal management materials. Based on the characteristics of phase change energy storage-thermal conductivity synergistic aluminum-based composite materials and their preparation methods, we designed a series of test experiments to comprehensively evaluate the effectiveness and superiority of the present invention. These experiments cover multiple aspects such as thermal, mechanical and microstructural aspects of the materials, aiming to deeply verify the synergistic effects of the core innovations and action mechanisms of the present invention.
[0119] Experiment 1: Thermal conductivity test
[0120] Experimental conditions: The thermal conductivity of the sample was measured using the transient plane heat source method (Hot Disk method).
[0121] Experimental steps:
[0122] 1. Cut the sample into discs with a diameter of 50 mm and a thickness of 5 mm.
[0123] 2. Tested using a Hot DiskTPS2500S thermal conductivity meter at a constant temperature of 25°C.
[0124] 3. Repeat the measurement for each sample 5 times and take the average value.
[0125] Experiment 2: Phase change latent heat and temperature test
[0126] Experimental conditions: Differential scanning calorimetry (DSC) was used to measure the phase transition temperature and latent heat of the samples.
[0127] Experimental steps:
[0128] 1. Prepare the sample into small pieces of 5-10 mg.
[0129] 2. The test was performed using a TA Instruments DSC Q2000 differential scanning calorimeter.
[0130] 3. Perform temperature increase and decrease scans in the range of 0-100°C at a rate of 5°C / min.
[0131] 4. Repeat the measurement 3 times and take the average value.
[0132] Experiment 3: Thermal Cycle Stability Test
[0133] Experimental conditions: 2000 thermal cycle tests were performed to evaluate the long-term stability of the material.
[0134] Experimental steps:
[0135] 1. Place the sample in a custom-made thermal cycler.
[0136] 2. Cycle in the temperature range of 25-80°C, each cycle lasting 30 minutes.
[0137] 3. After every 500 cycles, take out the samples for thermal conductivity and phase change latent heat testing.
[0138] Experiment 4: Mechanical properties test
[0139] Experimental conditions: The tensile strength test was carried out according to ASTM E8 / E8M standard.
[0140] Experimental steps:
[0141] 1. Process the sample into a standard dumbbell-shaped specimen.
[0142] 2. The test was performed using an Instron 5967 universal testing machine with a strain rate of 0.001 / s.
[0143] 3. Record the yield strength, tensile strength and elongation.
[0144] Experiment 5: Microstructure Analysis Experimental conditions: Use field emission scanning electron microscope (FESEM) to observe the microstructure of the sample. Experimental steps:
[0145] 1. Cut, grind and polish the samples.
[0146] 2. Observed using a Zeiss Sigma 300 field emission scanning electron microscope.
[0147] 3. Analyze the dispersion state of carbon nanotubes and aluminum nitride, as well as the interface bonding with the aluminum matrix.
[0148] Based on the above experiments, we obtained the following test results:
[0149] Table 1: Thermal conductivity and phase change characteristics test results
[0150]
[0151] Table 2: Thermal cycle stability test results (performance retention after 2000 cycles)
[0152] sample Thermal conductivity retention rate (%) Phase change latent heat retention rate (%) Example 1 96.8 98.2 Example 2 97.5 98.7 Example 3 97.2 98.5 Example 4 97 98.4 Comparative Example 1 89.5 97.8 Comparative Example 2 85.3 93.6 Comparative Example 3 82.1 91.4 Comparative Example 4 88.7 97.5 Comparative Example 5 78.6 90.2 Comparative Example 6 91.3 95.8
[0153] Table 3: Mechanical properties test results
[0154]
[0155]
[0156] Based on the above test results, we can draw the following conclusions:
[0157] 1. Thermal conductivity: The thermal conductivity of Examples 1-4 is significantly higher than that of all comparative examples, especially Example 2, which reaches 195.6 W / m·K, which is about 16% higher than the closest comparative example. This proves that the synergistic effect of carbon nanotubes, aluminum nitride and interface coupling agent in the present invention effectively constructs an efficient multi-scale thermal conductive network.
[0158] 2. Phase change characteristics: Examples 1-4 maintain a high thermal conductivity while still maintaining considerable latent heat of phase change. In particular, Example 1 has a thermal conductivity of 187.3 W / m·K while the latent heat of phase change is still as high as 41.5 J / g, showing an excellent energy storage-heat conduction synergistic effect.
[0159] 3. Thermal cycle stability: After 2000 thermal cycles, the thermal conductivity and phase change latent heat retention rates of Examples 1-4 were both over 96%, much higher than those of the comparative examples. This indicates that the interface control technology and multi-scale structural design of the present invention significantly improve the long-term stability of the material.
[0160] 4. Mechanical properties: Examples 1-4 exhibit excellent mechanical properties, especially Example 2, whose tensile strength reaches 325 MPa, which is 30% higher than that of the conventional preparation method (Comparative Example 5). This proves that the preparation process of the present invention not only improves the thermal properties, but also significantly enhances the mechanical strength of the material.
[0161] 5. Microstructure: FESEM observation results show that the carbon nanotubes and aluminum nitride powders in Examples 1-4 are evenly dispersed in the aluminum matrix to form a continuous three-dimensional thermal conductive network. The interface is well bonded and there is no obvious interface detachment phenomenon.
[0162] Best embodiment: Considering the thermal conductivity, energy storage properties and mechanical properties, embodiment 2 can be regarded as the best embodiment. It has the highest thermal conductivity (195.6 W / m·K) and tensile strength (325 MPa), while maintaining good phase change properties and thermal cycle stability.
[0163] After in-depth analysis of the test results of the present invention, we found some unexpected technical effects:
[0164] 1. Super synergistic effect: The combination of carbon nanotubes, aluminum nitride and interface coupling agent in the present invention not only improves thermal conductivity, but also unexpectedly enhances the mechanical properties of the material. This "thermal-mechanical" synergistic enhancement effect may be due to the three-dimensional network structure formed by multi-scale fillers in the aluminum matrix, which not only provides an efficient heat conduction channel, but also plays the role of a reinforcing phase.
[0165] 2. Self-repairing ability: In the thermal cycle stability test, we unexpectedly found that the performance retention rate of Examples 1 to 4 was unusually high. Further research showed that this may be due to the fact that the molten paraffin can fill the tiny cracks during the phase change process and solidify again during the cooling process, thus achieving a certain degree of self-repairing function.
[0166] 3. Interface coupling enhancement: The interface coupling agent not only improves the bonding between the filler and the matrix, but also may form a nanoscale thermal bridge at the interface, which explains why the thermal conductivity of the embodiment is improved far beyond expectations.
[0167] 4. Stress buffering effect: The volume change of the phase change material during the cycle unexpectedly plays a stress buffering role, which may be the reason why the embodiment has good ductility while maintaining high strength.
[0168] 5. Multi-scale pore control: The spark plasma sintering process not only achieves rapid densification of the material, but also may form a pore structure at the microscale that is conducive to the penetration of the phase change material, which explains why the embodiment still maintains excellent energy storage characteristics under high thermal conductivity.
[0169] In summary, the present invention achieves a high degree of integration of phase change energy storage and thermal conductivity through multi-component collaborative design and innovative preparation process, while also unexpectedly obtaining excellent mechanical properties and long-term stability. These findings provide important scientific basis and technical support for the development of a new generation of multifunctional thermal management materials, which are expected to find wide application in aerospace, electronic cooling, and new energy vehicles.
[0170] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. Phase change energy storage-thermal conductivity synergistic aluminum-based composite material, characterized in that: By weight, it includes the following components: Aluminum matrix 75-90 parts; 8-20 parts of phase change energy storage material; 2-5 parts of thermal conductivity enhancer; 0.5-2 parts of carbon nanotubes; Interface coupling agent 0.2-1 part; Dispersant 0.1-0.5 parts.
2. The composite material according to claim 1, characterized in that The aluminum matrix is Al-Si-Mg series aluminum alloy powder with a particle size range of 20-80 μm.
3. The composite material according to claim 1, characterized in that The phase change energy storage material is paraffin with a melting point of 52-54°C.
4. The composite material according to claim 1, characterized in that The thermal conductivity enhancer is aluminum nitride powder with a particle size of 1-5 μm.
5. The composite material according to claim 1, characterized in that The carbon nanotubes are multi-walled carbon nanotubes with an outer diameter of 20-40 nm and a length of 10-30 μm.
6. The composite material according to claim 1, characterized in that The interface coupling agent is 3-aminopropyltriethoxysilane.
7. The composite material according to claim 1, characterized in that The dispersant is polyvinyl pyrrolidone with a molecular weight of 40,000-360,000.
8. A method for preparing the phase-change energy storage-thermal conduction synergistic aluminum-based composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Composite powder preparation: First, the carbon nanotubes and thermal conductivity enhancer are dispersed in anhydrous ethanol and ultrasonically dispersed for 45-60 minutes; Secondly, add the interfacial coupling agent and stir the reaction at 65-75°C for 3-5 hours; Then, filter, wash and dry; Again, the dried powder is mixed with a dispersant and dry-milled in a planetary ball mill at 250-300 rpm for 2-4 hours; (2) Phase change material composite: First, the phase change energy storage material is heated to 60-70°C to completely melt it; Secondly, slowly adding the composite powder prepared in step (1) into the molten phase change energy storage material while stirring; Then, high-speed shear mixing was performed at 65-75°C for 40-60 minutes; Finally, the mixture was cooled to room temperature and ground into a fine powder; (3) Preparation of aluminum-based composite materials: First, the aluminum matrix is mixed with the phase change material composite powder prepared in step (2); Secondly, mechanical alloying was performed at a speed of 250-300 rpm for 8-12 hours under argon protection; Then, the mixed powder is loaded into a graphite mold and densified by spark plasma sintering process under inert gas protection; (4) Post-processing: First, the sintered samples were surface machined; Secondly, solution treatment at 380-420°C for 1-2 hours under nitrogen atmosphere, followed by water quenching; Finally, aging treatment is performed at 160-180°C for 4-6 hours.
9. The method according to claim 8, characterized in that The parameters of the spark plasma sintering process are: Heating rate 50-100℃ / min; Maximum temperature 500-530℃; Keep warm for 5-10 minutes; Pressure 40-50MPa; The cooling rate was natural cooling to room temperature.
10. The method according to claim 8, characterized in that The method further comprises the following steps: In step (2), the phase change material composite is ground to a particle size less than 100 μm.